NELLIE: Never-Ending Linking for Linked Open Data - Ahmed, Abdullah Fathi; Sherif, Mohamed Ahmed; Ngomo, Axel-Cyrille Ngonga (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science; Electrical and Electronic Engineering

Using Pre-trained Language Models for Abstractive DBpedia Summarization: A Comparative Study - Zahera, Hamada Mohamed Abdelsamee; Vitiugin, Fedor; Sherif, Mohamed; Castillo, Carlos; Ngonga Ngomo, Axel-Cyrille (SEMANTiCS)
Purpose: This study addresses the limitations of current short abstracts of DBpedia entities, which often lack a comprehensive overview due to their creating method (i.e., selecting the first two-three sentences from the full DBpedia abstracts). Methodology: We leverage pre-trained language models to generate abstractive summaries of DBpedia abstracts in six languages (English, French, German, Italian, Spanish, and Dutch). We performed several experiments to assess the quality of generated summaries by language models. In particular, we evaluated the generated summaries using human judgments and automated metrics (Self-ROUGE and BERTScore). Additionally, we studied the correlation between human judgments and automated metrics in evaluating the generated summaries under different aspects: informativeness, coherence, conciseness, and fluency. Findings: Pre-trained language models generate summaries more concise and informative than existing short abstracts. Specifically, BART-based models effectively overcome the limitations of DBpedia short abstracts, especially for longer ones. Moreover, we show that BERTScore and ROUGE-1 are reliable metrics for assessing the informativeness and coherence of the generated summaries with respect to the full DBpedia abstracts. We also find a negative correlation between conciseness and human ratings. Furthermore, fluency evaluation remains challenging without human judgment. Value: This study has significant implications for various applications in machine learning and natural language processing that rely on DBpedia resources. By providing succinct and comprehensive summaries, our approach enhances the quality of DBpedia abstracts and contributes to the semantic web community
Keywords: dice enexa kiam ngonga porque sherif zahera

IngridKG: A FAIR Knowledge Graph of Graffiti - Sherif, Mohamed; Morim da Silva, Ana Alexandra; Pestryakova, Svetlana; Ahmed, Abdullah Fathi Ahmed; Niemann, Sven; Ngonga Ngomo, Axel-Cyrille
Graffiti is an urban phenomenon that is increasingly attracting the interest of the sciences. To the best of our knowledge, no suitable data corpora are available for systematic research until now. The Information System Graffiti in Germany project (Ingrid) closes this gap by dealing with graffiti image collections that have been made available to the project for public use. Within Ingrid, the graffiti images are collected, digitized and annotated. With this work, we aim to support the rapid access to a comprehensive data source on Ingrid targeted especially by researchers. In particular, we present IngridKG, an RDF knowledge graph of annotated graffiti, abides by the Linked Data and FAIR principles. We weekly update IngridKG by augmenting the new annotated graffiti to our knowledge graph. Our generation pipeline applies RDF data conversion, link discovery and data fusion approaches to the original data. The current version of IngridKG contains 460,640,154 triples and is linked to 3 other knowledge graphs by over 200,000 links. In our use case studies, we demonstrate the usefulness of our knowledge graph for different applications.

Multiprotein Adsorption from Human Serum at Gold and Oxidized Iron Surfaces Studied by Atomic Force Microscopy and Polarization-Modulation Infrared Reflection Absorption Spectroscopy - Huang, Jingyuan; Qiu, Yunshu; Lücke, Felix; Su, Jiangling; Grundmeier, Guido; Keller, Adrian (Molecules)
Multiprotein adsorption from complex body fluids represents a highly important and complicated phenomenon in medicine. In this work, multiprotein adsorption from diluted human serum at gold and oxidized iron surfaces is investigated at different serum concentrations and pH values. Adsorption-induced changes in surface topography and the total amount of adsorbed proteins are quantified by atomic force microscopy (AFM) and polarization-modulation infrared reflection absorption spectroscopy (PM-IRRAS), respectively. For both surfaces, stronger protein adsorption is observed at pH 6 compared to pH 7 and pH 8. PM-IRRAS furthermore provides some qualitative insights into the pH-dependent alterations in the composition of the adsorbed multiprotein films. Changes in the amide II/amide I band area ratio and in particular side-chain IR absorption suggest that the increased adsorption at pH 6 is accompanied by a change in protein film composition. Presumably, this is mostly driven by the adsorption of human serum albumin, which at pH 6 adsorbs more readily and thereby replaces other proteins with lower surface affinities in the resulting multiprotein film.
Keywords: Chemistry (miscellaneous); Analytical Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Molecular Medicine; Drug Discovery; Pharmaceutical Science

Adsorption of Ferritin at Nanofaceted Al2O3 Surfaces - Pothineni, Bhanu K.; Kollmann, Sabrina; Li, Xinyang; Grundmeier, Guido; Erb, Denise J.; Keller, Adrian (International Journal of Molecular Sciences)
The influence of nanoscale surface topography on protein adsorption is highly important for numerous applications in medicine and technology. Herein, ferritin adsorption at flat and nanofaceted, single-crystalline Al2O3 surfaces is investigated using atomic force microscopy and X-ray photoelectron spectroscopy. The nanofaceted surfaces are generated by the thermal annealing of Al2O3 wafers at temperatures above 1000 °C, which leads to the formation of faceted saw-tooth-like surface topographies with periodicities of about 160 nm and amplitudes of about 15 nm. Ferritin adsorption at these nanofaceted surfaces is notably suppressed compared to the flat surface at a concentration of 10 mg/mL, which is attributed to lower adsorption affinities of the newly formed facets. Consequently, adsorption is restricted mostly to the pattern grooves, where the proteins can maximize their contact area with the surface. However, this effect depends on the protein concentration, with an inverse trend being observed at 30 mg/mL. Furthermore, different ferritin adsorption behavior is observed at topographically similar nanofacet patterns fabricated at different annealing temperatures and attributed to different step and kink densities. These results demonstrate that while protein adsorption at solid surfaces can be notably affected by nanofacet patterns, fine-tuning protein adsorption in this way requires the precise control of facet properties.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Neural Class Expression Synthesis (Extended Abstract) - Kouagou, N’Dah Jean; Heindorf, Stefan; Demir, Caglar; Ngomo, Axel-Cyrille Ngonga (NeSy)

Life-cycle health effects of compulsory schooling - Schmitz, Hendrik; Tawiah, Beatrice Baaba
We study the effect of education on health (hospital stays, number of diagnosed conditions, self-rated poor health, and obesity) over the life-cycle in Germany, using compulsory schooling reforms as a source of exogenous variation. Our results suggest a positive correlation of health and education which increases over the life-cycle. We do not, however, find any positive local average treatment effects of an additional year of schooling on health or health care utilization for individuals up to age 79. An exception is obesity, where positive effects of schooling start to be visible around age 60 and become very large in age group 75-79. The results in age group 75-79 need to be interpreted with caution, however, due to small sample size and possible problems of attrition.
Keywords: Education; health; life-cycle effects; compulsory schooling

Housing Situations and Local COVID-19 Infection Dynamics – A Case Study With Small-Area Data - Freise, Diana; Schiele, Valentin; Schmitz, Hendrik
Keywords: General Earth and Planetary Sciences; General Environmental Science

Partial observations, coarse graining and equivariance in Koopman operator theory for large-scale dynamical systems - Peitz, Sebastian; Harder, Hans; Nüske, Feliks; Philipp, Friedrich; Schaller, Manuel; Worthmann, Karl (arXiv:2307.15325)
The Koopman operator has become an essential tool for data-driven analysis, prediction and control of complex systems, the main reason being the enormous potential of identifying linear function space representations of nonlinear dynamics from measurements. Until now, the situation where for large-scale systems, we (i) only have access to partial observations (i.e., measurements, as is very common for experimental data) or (ii) deliberately perform coarse graining (for efficiency reasons) has not been treated to its full extent. In this paper, we address the pitfall associated with this situation, that the classical EDMD algorithm does not automatically provide a Koopman operator approximation for the underlying system if we do not carefully select the number of observables. Moreover, we show that symmetries in the system dynamics can be carried over to the Koopman operator, which allows us to massively increase the model efficiency. We also briefly draw a connection to domain decomposition techniques for partial differential equations and present numerical evidence using the Kuramoto--Sivashinsky equation.

The effect of compulsory schooling on vaccination against COVID and Influenza - Monsees, Daniel; Schmitz, Hendrik
We study the effect of education on vaccination against COVID-19 and influenza in Germany and Europe. Our identification strategy makes use of changes in compulsory schooling laws and allows to estimate local average treatment effects for individuals between 59 and 91 years of age. We find no significant effect of an additional year of schooling on vaccination status in Germany. Pooling data from Europe, we conclude that schooling increases the likelihood to vaccinate against COVID by an economically negligible effect of one percentage point (zero for influenza). However, we find indications that additional schooling increases fear of side effects from COVID vaccination.
Keywords: COVID; influenza; vaccination; education; compulsory schooling

NeMo.bil - Dekarbonisierung des Verkehrs mithilfe von Leichtbau-Fahrzeugschwärmen - Ostermann, Moritz; Behm, Jonathan; Marten, Thorsten; Tröster, Thomas (WerkstoffPlus Auto 13. Fachtagung für neue Fahrzeug- und Werkstoffkonzepte)

16 Fragen, 16 Antworten: In unserer Rubrik „Lehren im Leben” stellen wir Menschen vor, die Hochschullehre gestalten. Folge 6: Dr. Nerea Vöing - Vöing, Nerea (Lehren im Leben - Blog der Stiftung Innovation in der Hochschullehre)

Ein Blick auf Lehre und Lernen in Hochschulen durch die Brille der Hochschuldidaktik" - Vöing, Nerea (Trafohaus//Lehre (Podcast der HD Sachsen))

Lehrentwicklung durch Scholarship of Teaching and Learning – mit SoTL Hochschullehre beforschen, weiterentwickeln und teilen - Vöing, Nerea; Arnold, Maik; Reisas, Sabine

Revisiting the initial reaction rates for TMS combustion and a new evidence for metastable silica nanoparticles in the gas-phase synthesis - Karakaya, Yasin; Somnitz, H.; Hermsen, A.; Gonchikzhapov, Munko; Kasper, Tina (Applications in Energy and Combustion Science)
Keywords: Metastable particles; Nanomaterials; Quartz-crystal-microbalance; Molecular-beam mass spectrometry; Tetramethylsilane; Reaction kinetics

Fiber-coupled plug-and-play heralded single photon source based on Ti:LiNbO3 and polymer technology - Kießler, Christian; Conradi, Hauke; Kleinert, Moritz; Quiring, Viktor; Herrmann, Harald; Silberhorn, Christine (Optics Express)
A reliable, but cost-effective generation of single-photon states is key for practical quantum communication systems. For real-world deployment, waveguide sources offer optimum compatibility with fiber networks and can be embedded in hybrid integrated modules. Here, we present what we believe to be the first chip-size fully integrated fiber-coupled heralded single photon source (HSPS) module based on a hybrid integration of a nonlinear lithium niobate waveguide into a polymer board. Photon pairs at 810 nm (signal) and 1550 nm (idler) are generated via parametric down-conversion pumped at 532 nm in the LiNbO3 waveguide. The pairs are split in the polymer board and routed to separate output ports. The module has a size of (2 × 1) cm^2 and is fully fiber-coupled with one pump input fiber and two output fibers. We measure a heralded second-order correlation function of g_h(2)=0.05 with a heralding efficiency of η_h=3.5% at low pump powers
Keywords: Atomic and Molecular Physics; and Optics

Scholarship of Teaching and Learning (SoTL) als Motor für eine inter- und transdisziplinäre Hochschuldidaktik - Arnold, Maik; Vöing, Nerea; Reisas, Sabine (Hochschulbildung: Lehre und Forschung)
SoTL ist eine forschungsbasierte Haltung, die die Hochschullehre verbessern und innovieren will. Das deutschsprachige SoTL-Netzwerk hat fünf Thesen formuliert, die SoTL als Grundhaltung und Motor für Lehrentwicklung betonen. Der Beitrag diskutiert diese Thesen und stellt Aktivitäten des Netzwerks vor, die SoTL an Hochschulen und Universitäten fördern und vernetzen wollen. Dabei wird auch die Rolle der »Teacher-Researcher« hervorgehoben.

Identification and prediction of standard times in machining for precision steel tubes through the usage of data analytics - Weller, Julian; Roesmann, Daniel; Eggert, Sönke; von Enzberg, Sebastian; Gräßler, Iris; Dumitrescu, Roman (Procedia CIRP)

Zur Berechnug von flüssigkeitsseitigen Stoffübergagnskoeffizienten für Strukturpackungen - Mapura Ramirez, Luz Alejandra; Kenig, Eugeny Y.

Finite-data error bounds for Koopman-based prediction and control - Nüske, Feliks; Peitz, Sebastian; Philipp, Friedrich; Schaller, Manuel; Worthmann, Karl (Journal of Nonlinear Science)
The Koopman operator has become an essential tool for data-driven approximation of dynamical (control) systems in recent years, e.g., via extended dynamic mode decomposition. Despite its popularity, convergence results and, in particular, error bounds are still quite scarce. In this paper, we derive probabilistic bounds for the approximation error and the prediction error depending on the number of training data points; for both ordinary and stochastic differential equations. Moreover, we extend our analysis to nonlinear control-affine systems using either ergodic trajectories or i.i.d. samples. Here, we exploit the linearity of the Koopman generator to obtain a bilinear system and, thus, circumvent the curse of dimensionality since we do not autonomize the system by augmenting the state by the control inputs. To the best of our knowledge, this is the first finite-data error analysis in the stochastic and/or control setting. Finally, we demonstrate the effectiveness of the proposed approach by comparing it with state-of-the-art techniques showing its superiority whenever state and control are coupled.